SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIANREKAM MEDIS DENGAN BARCODE DAN NOTIFIKASI WHATSAPP DI RUMAH SAKIT WIJAYA KUSUMA LUMAJANG - Hayu Ning Widyastuti; Andri Permana Wicaksono; Sustin Farlinda; Ervina Rachmawati (Politeknik Negeri Jember, 2020)
The medical record file control activity at Wijaya Kusuma Lumajang Hospital has not been well implemented.This is evidenced by the absence of the use of tracers as a substitute for files that leave the medical recordrack and the use of expedition books only on borrowing inpatient medical record files. This study aims todesign and create a medical record lending and return information system with a barcode and web-basedWhatsApp notification at Wijaya Kusuma Lumajang Hospital that produces patient labels, tracers, reports onborrowing and return of medical records. This type of research is the development of a prototype method withqualitative data collection techniques in the form of interviews, observation, documentation, and brainstorming.The stages of the prototype method include analyzing user needs, making prototypes, adjusting prototypes tothe user's wishes, creating new systems, testing systems, adjusting the system to the user's wishes, andusing the system. The results of this study are information systems for borrowing and returning medicalrecords with a web-based barcode and WhatsApp notification system that facilitates the process of trackingfiles and overcoming problems in the process of borrowing and returning medical records